Observations on the ultrastructure of a rat mammary gland treated with harmal and borage - Al- Yawer, Malak A.; Al- Saidi, Wasan; Al-Faisaly, Shatha M.; Hamoudi, Salim R. (Journal of the Faculty of Medicine Baghdad, 2007)
Background : It had been indentified by histological, histochemical and morphometrical studies that peganum harmala is a mammogenic herb and borage officinalis is a lactogenic one . To complete our investigation about these two herbs , we performed electron microscopical study.Materials and methods : Rats were grouped according to their physiological status into three groups . Each group was subdivided in to three subgroups : one control and two experimental . The two experimental group were treated daily; the 1st one with an aqueous extract of peganum harmala seeds and the 2nd with an aqueous extract of borage officinalis flowers . After two weeks of treatment , mammary glands were employed for electron microscopical study.Results : In virgin rats , the epithelial and myoepithelial cells were partially differentiated when harmal was given and completely differentiated when borage was given . In pregnant rats , harmal and borage optimize mammary parenchymal growth and induce lactation when these herbs were given. In lactating rats ,these herbs exhibited a picture similar to control lactating group but the budding of lipid droplets and the swelling of secretary vesicles were markedly increased.Conclusion: Both harmal and borage stimulate the release of prolactin and induce galactogenesis during pregnancy and promote it during lactation .